Conflicts around Germany’s Energiewende: Discourse patterns of citizens’ initiatives - Weber, Florian; Jenal, Corinna; Rossmeier, Albert; Kühne, Olaf (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
Especially since the Fukushima nuclear catastrophe (2011), Germany has expanded its renewably sourced energies. Nuclear power is to be phased out by 2022. What is central to federal policy is the expansion of wind-generated energy. Plans for new wind farms have, however, faced opposition. And the transportation of electricity from the windy north to the high-use south entails an expansion of the existing power grid, which also provokes conflict. The article scrutinises dominant patterns of discourse on these issues. Based on current discourse theory, the research sheds light on the argumentative power of citizens’ initiatives with respect to nature conservation, landscape, health and economics.
Keywords: renewable energies; Germany; wind energy; power grid extension; citizens’ initiatives